Write modern web apps with the MEAN stack (Learn by video., 2014)
"The MEAN stack (Mongo, Express, AngularJS, and Node.js) offers a new path to writing web applications by treating the front-end as if it were a third-party (such as a mobile client). This video by full-stack developer Jeff Dickey takes a holistic approach to learning the MEAN JavaScript platform and shows how to build, test, and deploy apps."--Resource description page.